Free Trade Area of the Americas : good for Latin America? - PANAGARIYA, Arvind (1996)
Points out the relevance of a mercantilist approach for the economics of free trade areas. Discusses some aspects of regional arrangements between developed and developing countries, and compares NAFTA to the European Union. Argues that Latin American countries will lose from the FTAA. Concludes that policy harmonisation within North-South regional schemes is a costly affair for southern countries.